0145 Clinical simulations: Students experiences of developing clinical judgment skills. (2nd November 2015) - Lesa, Raewyn; Daniel, Ben; Harland, Tony
Abstract : Background/context: Teaching in clinical simulations potentially supports students to develop varied skills sets including teamwork, therapeutic communication, critical thinking and clinical judgment. 1 Research into understanding the effectiveness of clinical simulations to develop clinical judgment is growing. 2, 3 However, little is known about students' experiences of developing clinical judgment skills in clinical simulations and how such skills are likely to translate to making clinical judgments in a clinical setting. The purpose of this research was to understand how students develop clinical judgment skills in clinical simulation-based learning environments. Methodology: To explore how undergraduate students develop clinical judgment skills a case study was used to pursue the research goal. Data was collected from March to June 2015. Twelve clinical simulations were observed and twelve participants interviewed twice; once after clinical simulations and again after clinical practice. Permission was given to record video for six of the observed clinical simulations. Additional data included crelated to clinical simulations. Anticipated outcomes: An understanding of the opportunities and challenges associated with acquiring clinical judgment skills in simulation-based learning environments in undergraduate nursing education An understanding of how a simulation learning context influences students development of clinical judgment skills An understanding of how to design simulations to influence students development of clinical judgment skills Potential impact: A contribution to the knowledge and theory to inform teaching practices in clinical simulations in undergraduate nursing programs. Implications for policy makers grappling with issues surrounding possible substitution of clinical hours with clinical simulations. References: Jeffries PR. Simulation in nursing education: from conceptualization to evaluation: National League for Nursing, 2012 Hayden JK, Smiley RA, Alexander M, Kardong-Edgren S, Jeffries PR. Supplement: The NCSBN national simulation study: a longitudinal, randomized, controlled study replacing clinical hours with simulation in prelicensure nursing education. J Nurs Regul. 2014;5(2):C1–S64 Kelly, MA. Investigating the use of simulations in enhancing clinical judgement of students to practice as registered nurses. Sydney: Faculty of Arts and Social Sciences, University of Technology, 2014